The Role of Consumer Behavior in Shaping Entrepreneurial Marketing Strategies in the Digital Age - Grant Evans; Boike Rehbein; Marc Askew (Global Management: International Journal of Management Science and Entrepreneurship, 2024)
This article investigates the evolving role of consumer behavior in shaping entrepreneurial marketing strategies in the digital age. The proliferation of social media, online platforms, and big data analytics has transformed how entrepreneurs engage with consumers. The study delves into how entrepreneurs use consumer insights to create personalized marketing strategies, foster customer loyalty, and enhance brand value. A qualitative analysis of case studies from various industries illustrates the impact of digital tools on marketing effectiveness. The paper provides insights on how entrepreneurs can better align their marketing approaches with changing consumer preferences in a rapidly evolving digital landscape.